GUGATAN YANG DINYATAKAN TIDAK DAPAT DITERIMA (STUDI PUTUSAN PHI BANDUNG NOMOR 171/PDT.SUS-PHI/2017/PN.BDG) - Alvira Zahra Hartono; Yogo Pamungkas; Hartono, Alvirazahra (Faculty of Law, Universitas Trisakti, 2023)
Termination of Employment Relations is the ending of employment relationships in a way that also terminates the company's and its employees' rights and obligations. Delivered by the PHI Bandung Number 171/Pdt.Sus-PHI/2017/PN.BDG Decision that the lawsuit brought by Plaintiff N.O A vague lawsuit (obscuur libel), in which the formulation of the lawsuit is not clear and it is therefore considered formally flawed, is one of the factors that lead to the lawsuit becoming formally flawed and not being accepted. The formulation of the problem is whether there is conformity with the Decision of the Bandung Industrial Relations Judge Regarding Lawsuit Disputes. The suit (Niet Onvankelijk Verklaard) will not accept termination of employment with Law Number 2 of 2004 concerning Settlement of Industrial Relations Disputes and whether Ikhsan Noviandi, S.H.. The research in a normative juridical manner based on literature studies and was analyzed qualitatively with deductive methods and secondary data. From the results of research, discussion and conclusions: The PHI decision is not in accordance with the existing provisions and it is possible for the Plaintiff to seek cassation on the Bandung PHI Decision Number 171/Pdt.Sus-PHI/2017/PN.BDG even though the Plaintiff did not submit such effort.